Embracing and escalating creativity and passion of FPHP family for writing / Irina Mohd Akhir - Mohd Akhir, Irina (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
Welcome, dear readers, to the latest edition of the Hot & Tour Newsletter! We are thrilled to have you join us once again as we dive into volume 2 for the year 2023 . In this November publication, we will be highlighting all the exciting happenings from December 2022 and throughout the year 2023 . Our tagline for this issue is " Together, we make it great! " and our goal is to provide you with valuable insights and updates on a regular basis . We want this newsletter to be both informative and engaging, so we hope you find it to be just that. Worry you may not, there are more editions to come, so stay tuned for the latest news and information.